Techno-Economic Analysis in The Production of Copper Nanoparticles with Chemical Reduction Methods using L-Ascorbic Acid - Rahmahani Alfathia Fadhilah; Muhammad Roil Bilad2 (Universitas Pendidikan Indonesia (UPI), 2022)
Copper nanoparticles (Cu-NPs) are a type of nanoparticles with various industrial applications. The synthesis of copper nanoparticles by the chemical reduction method is environmentally friendly, simple, and produces better nanoparticles compared to other methods. This study aims to determine the feasibility of a Cu nanoparticle manufacturing project through a chemical reduction method using L-ascorbic acid on an industrial scale and evaluate it from an engineering and economic perspective. Technical analysis is carried out using a simple balance sheet analysis while the economic evaluation is carried out using several economic parameters, such as Payback Period (PBP), Break-even Point (BEP), and Cumulative Net Present Value (CNPV). The carried-out analysis is supported by using data taken based on the availability of tools on online shopping websites. The results of the study show that this project is profitable and feasible to run with the anticipation of taxes and sales. This research is expected to provide an industrial scale representation of the economic evaluation and plan of the production of Cu nanoparticles by chemical reduction method using L-Ascorbic Acid.